Hemophilia A in Brazil – epidemiology and treatment developments - Ferreira, Adriana Aparecida (Dove Medical Press, 2014)
Hemophilia A is an inherited disorder characterized by deficiency of coagulation factor VIII, which predisposes patients to bleeding events. Treatment is based on replacement of the deficient factor, in a therapeutic or prophylactic manner. Brazil is the country with the third largest population of people with hemophilia, for which the public health system provides free comprehensive care. Maintaining an updated registry of patients, documenting the prevalence of complications, and assessing the effectiveness of resource use are indispensable elements in the design of a well-coordinated national program. According to sociodemographic, clinical, and laboratory data collected by the computerized Brazilian system on coagulopathies, in June 2013, there were 9,122 registered patients with hemophilia A in Brazil, of which 36.1% had a severe form of the disease. Clotting factor inhibitors were present in 7.5%, but 25.7% of records did not provide this type of data. Around 70% of the patients belonged to the economically active population, being between 15 and 59 years old. Infection by the human immunodeficiency virus was present in 23.4% of the patients tested and infection by hepatitis C virus antibodies in 59.3%. Infection by the hepatitis B virus and human T-lymphotropic virus was also reported. The high percentage of incomplete records regarding serological data shows the fragility of the information system to date. There was also no information available on the prevalence of permanent or disabling joint damage. Although few hemophiliacs receive adequate care in developing countries, and despite Brazil exhibiting great social inequalities, the Ministry of Health has made significant advances in the treatment of hemophilia A. The gradual increase in importation of factor VIII concentrate enabled the implementation of primary and secondary modalities of prophylaxis, in addition to the induction of immune tolerance. There are also plans to set up a factory in the country, to ensure Brazilian self-sufficiency in the production of blood products.